The Characteristics of Padamarang Magnesite under Calcination and Hydrothermal Treatment - Mutia Dewi Yuniati; Feronika Cinthya Mawarni Putri Wawuru; Anggoro Tri Mursito; Iwan Setiawan; Lediyantje Lintjewas (Indonesian Institute of Sciences, 2019)
Magnesite (MgCO3) is the main source for production of magnesium and its compound. In Indonesia, magnesite is quite rare and can be only found in limited amount in Padamarang Island, Southeast Sulawesi Provence. Thus the properties of magnesite and the reactivity degree of the obtained product are of technological importance. The aim of this work was to analyze the characteristics of Padamarang magnesite under calcination and hydrothermal treatment processes. The processes were carried out at various temperatures with range of 150-900°C for 30 minutes. The solids were characterized with respect to their chemical and physical properties by using scanning electron microscopy with energy-dispersive X-ray spectroscopy (SEM-EDX), Fourier-transform infrared spectroscopy (FTIR), and X-ray diffraction (XRD). SEM image indicates that magnesite was formed from thin and flat hexagon sheets. The FTIR and XRD analysis disclose that MgO formed at temperature above 300°C, where as the magnesite sample also lost its mass around 50%. These results demonstrate that Padamarang magnesite decomposes to magnesium oxide and carbon dioxide at high temperature.Magnesit (MgCO3) merupakan sumber utama untuk produksi magnesium dan senyawa-senyawanya. Di Indonesia, magnesit cukup jarang dan hanya dapat ditemukan dalam jumlah yang terbatas di Pulau Padamarang, Propinsi Sulawesi Tenggara. Oleh karena itu sifat magnesit dan derajat reaktivitas dari produk-produk magnesit penting untuk diketahui. Penelitian ini bertujuan untuk menganalisis karakteristik magnesit Padamarang dengan perlakuan kalsinasi dan hidrothermal. Proses dilakukan pada temperatur yang bervariasi dari 150-900°C selama 30 menit. Sifat kimia dan fisika dari magnesit dikarakterisasi dengan menggunakan scanning electron microscopy dengan energy-dispersive X-ray spectroscopy (SEM-EDX), Fourier-transform infrared spectroscopy (FTIR), dan X-ray diffraction (XRD). Gambar dari analisis SEM menunjukkan bahwa magnesit terbentuk dari lembaran-lembaran heksagonal yang tipis dan datar. Hasil analisis dengan FTIR dan XRD menunjukkan bahwa MgO terbentuk pada temperatur diatas 300°C, dimana sampel magnesit juga kehilangan massanya sekitar 50% pada suhu tersebut. Hal ini menunjukkan bahwa Magnesit Padamarang terdekomposisi menjadi magnesium oksida dan karbon dioksida pada temperatur tinggi.